Od redakcji - Martinez, Enrique; Prieto, Lucas; Manresa, Ignacio M. (Biblica et Patristica Thoruniensia, 2024)
To commemorate the jubilee of the death and canonization of St. Thomas Aquinas, the Santo Tomás Institute of Balmesiana organized the 10th Symposium of Thomistic Studies, St. Thomas Aquinas, Master of the Sacred Page. The event took place at the Abat Oliba CEU University in Barcelona from May 10th to 12th, 2024. Other institutions, in particular, the Association pour le Centenaire Thomas d’Aquin (ACTA) from Toulouse, contributed greatly to the organization of the symposium. This event aimed to explore St. Thomas’ use of Sacred Scripture in his role as a biblical scholar. This is one of the aspects of the doctrine of Aquinas that has recently gained prominence, as there has been a renewed appreciation for the central role that Sacred Scripture played in the theology of the Angelic Doctor, frequently referred to as “biblical Thomism”. The purpose of the symposium was not only historical but also doctrinal, aiming to shed light on contemporary biblical hermeneutics and exegesis. The symposium was structured around the three core activities of the medieval scholar: legere, disputare, and praedicare, with the intention to understand the place of Sacred Scripture in each of these. It began with several introductory issues that addressed Aquinas’ biblical hermeneutics and its foundations, with enriching contributions from professors Martínez, Amado, Loiseau, and Manresa. Next, the symposium delved into Aquinas’ biblical exegesis, focusing on his commentaries on St. John, St. Paul, and a book of the Old Testament, with insightful presentations by Professors Giambrone, Roszak, and Ossandón. The following sessions were dedicated to the examination of how St. Thomas utilized disputare in his construction of a theological system. Professors Margelidon, Aroztegi, and Prieto offered valuable reflections on grace, the sacraments, and divine knowledge. Finally, the symposium turned to Aquinas’ praedicare and his use of Scripture in preaching, with illuminating presentations by professors Smith, Vijgen, and Perrin. Thomas Olivier Venard concluded the symposium by discussing the contemporary relevance of Aquinas’ biblical hermeneutics. We are pleased to offer the reader a substantial number of these enriching contributions in both this and the next issue of Bíblica et Patristica. We are grateful to the Editorial Board for their willingness to publish the texts and, in this way, familiarise the readers with the fruitful discussions we experienced in Barcelona in May.